Green Hydrogen Production based on Biogas Reforming Integrated with Membrane-based CO2 Capture - Calin-Cristian Cormos; Letitia Petrescu; Ana-Maria Cormos (Chemical Engineering Transactions)
Renewable energy sources and the Carbon Capture, Utilization and Storage (CCUS) technologies are foreseen to play a fundamental role in an overall decarbonized economy in view of achieving the global climate neutrality. This work evaluates the technical and environmental implications of the green hydrogen production from biogas reforming process integrated with CO2 capture using membrane-based systems. The evaluated concepts have a capacity of 100 MWth green hydrogen with pre-combustion and post-combustion CO2 capture. The mass and energy balances of decarbonized biogas reforming design were then used to quantify the key performance indicators. For comparison reasons, the biogas reforming process without decarbonization feature and with CO2 capture based on chemical gas-liquid absorption were considered as benchmark cases. Detailed techno-economic and environmental analysis underlines the promising potential of green hydrogen production based on biogas reforming integrated with membrane-based CO2 capture feature: high cumulative energy efficiency (about 55 - 60 %), low specific CO2 emissions (down to 2 kg/MWh as process emission and negative emissions for the overall decarbonized biogas reforming system), co-generation capability of green hydrogen and decarbonized power as well as positive key economic indicators (e.g., specific investment cost, operational cost, levelized hydrogen production cost etc.) compared to the current fossil-based state of the art systems.